Morphological And Molecular Characterization Of Colletotrichum Species Isolated From Anthracnose Of Red-Fleshed Dragon Fruit (Hylocereus Polyrhizus) - Vijaya, Suzianti Iskandar (2014)
Red-fleshed dragon fruit (Hylocereus polyrhizus) is regarded as a health fruit crop and can bring high economic returns to Malaysia. The cultivation areas of this crop is increasing yearly and is now widely cultivated in Malaysia. However, H. polyrhizus is vulnerable towards multiple diseases caused by fungi, bacteria and virus, which is the major problem for H. polyrhizus cultivation in Malaysia. One of the important diseases caused by fungi infecting H. polyrhizus is anthracnose caused by Colletotrichum species. Thus, the main objectives of this study were to isolate, identify and characterize the Colletotrichum species associated with anthracnose of H. polyrhizus. The analyses were based on morphological characteristics, DNA sequencing of Internal Transcribed Spacer regions (ITS+5.8S) and β-tubulin gene, the genetic variation among the Colletotrichum isolates using phylogenetic analysis of ITS+5.8S and β-tubulin sequences and pathogenicity test. A total of 73 isolates of Colletotrichum were recovered from diseased H. polyrhizus stems from six states (Johor, Kedah, Negeri Sembilan, Pahang, Pulau Pinang and Selangor) in Peninsular Malaysia. Based on morphological characteristics, 63 isolates were identified as C. gloeosporioides and 10 isolates were identified as C. truncatum. Basic Local Alignment Search Tool (BLAST) similarity search of ITS+5.8S and ß-tubulin sequences confirmed the identity of morphologically identified C. gloeosporioides (63 isolates) and C. truncatum (10 isolates). Based on phylogenetic analysis, C. gloeosporioides and C. truncatum isolates were divided into two separate groups.